Performance, Immune Responses, and Blood Biochemistry of Broiler Chickens Fed with Plant Growth Compound - A. Mohseni Gharechopogh; J. Fakhraei; S. A. Hosseini; H. Mansoori Yarahmadi; H. Lotfollahian (Faculty of Animal Science, Bogor Agricultural University, 2021)
Today, medicinal plants and prebiotics are known as growth stimulants and can have beneficial effects on health and performance. This study was conducted to evaluate the effects of plant growth promoters and a prebiotic (lactose) on growth performance, immune responses, and blood biochemical parameters in broiler chicks. Seven hundred and fifty Arian broiler chicks (mixed-sex) were allocated to six treatments and five replicates at one day of age. Three plant-based growth promoters (ASRI1, ASRI2, and commercial supplement (Optifeed)) and two dietary prebiotic levels (0 and 1 kg/ton) were evaluated in a completely randomized design with 3×2 factorial arrangements. The results showed that growth performance and humoral and cellular immunities did not differ among experimental treatments; therefore, the herbal compounds ASRI1 and ASRI2 can be used as growth promoters equivalent to the commercial products currently used in the broiler chicken industry. An interaction effect of growth promoter × prebiotic was detected for concentrations of calcium in the serum. Serum calcium concentrations of birds fed ASRI2 and 1 kg/ton prebiotic were greater than those of chickens receiving the commercial growth promoter. Serum triglycerides and VLDL-C concentrations were significantly lower in birds treated with ASRI1 growth promoter compared to those fed with a commercial growth promoter. In conclusion, there was no difference between ASRI1, ASRI2, and Optifeed growth promoters in their effectiveness as promoters of growth and immunity of broiler chicks.